Study on knee joint isokinetic strength of male volleyball players - Shu, W. P.; Zhou, J. H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study is to measure the knee joint mechanics of eight elite volleyball players using isokinetic system and to discuss the possible diagnosis of injury risk of the results. Isokinetic-concentric contraction peak torque of the knee flexors and extensors decreased when angular velocity increased. With the same angular velocity, extension peak torque became higher than flexion peak torque. There was also a significant difference between the left and right knees in each flexion and extension peak torques. As the angular velocity increased, the flexion to extension peak torque ratios decreased; at the same time, average power increased while the work done decreased. The extensors showed greater work done than the flexors. The knee torque curves could be used as evidence for diagnosis of possible knee injury risks among volleyball players.